Clinical effectiveness and safety of additional administration of tacrolimus in rheumatoid arthritis patients with an inadequate response to abatacept: A retrospective cohort study. (24th October 2019) - Suzuki, Mochihito; Takahashi, Nobunori; Kida, Daihei; Hirano, Yuji; Kato, Takefumi; Yabe, Yuichiro; Oguchi, Takeshi; Fujibayashi, Takayoshi; Hayashi, Masatoshi; Asai, Shuji; Ishiguro, Naoki; Kojima, Toshihisa
Abstract: Objective: Abatacept (ABT) demonstrates good clinical efficacy and retention in rheumatoid arthritis (RA) patients. However, no rescue treatment option against inadequate response to ABT exists. Since tacrolimus (TAC) and ABT suppress T lymphocytes via different mechanisms and a combination of these agents could potentially be effective, this study aimed to examine the efficacy and safety of add‐on TAC therapy in RA patients with inadequate response to ABT. Methods: Of 550 patients treated with ABT and registered in a Japanese multicenter registry, 25 consecutive patients who underwent add‐on TAC therapy and were followed for longer than 24 weeks were included in this study. Results: Mean patient age was 67.0 years, disease duration was 16.2 years, and duration of ABT treatment was 1.2 years at the initiation of add‐on TAC therapy. Mean TAC dose was 1.2 mg/d at baseline and 1.6 mg/d at week 24. Mean Disease Activity Score of 28 joints – erythrocyte sedimentation rate was significantly improved at week 24 (3.35) relative to baseline (4.97). The proportion of patients who achieved low disease activity or remission was 40.0%, and the European League Against Rheumatism moderate or good response was 72.0%. ABT retention rate was 92.0% at week 24, as calculated by Kaplan‐Meier analysis. Only one patient discontinued add‐on TAC therapy due to an adverse event (itching sensation). Conclusion: This is the first report describing the efficacy and safety profile of add‐on TAC therapy with a focus on RA patients with inadequate response to ABT. Our findings suggest that add‐on TAC therapy is a worthwhile complementary treatment option in daily clinical practice.